Multiple Sclerosis and Schizophrenia - Arneth, Borros M. (Int J Mol Sci, 2017)
The psychiatric and neurological aspects of health may present methodological challenges in the diagnosis and treatment of disease. This is especially true for patients whose symptoms indicate the coexistence of multiple sclerosis (MS) and schizophrenia (SCZ). These cases raise critical questions regarding the relationship between the mind and the brain. Studies have noted that patients with MS have an increased risk of developing SCZ or bipolar disorder (BD). It is suggested here that MS and a subgroup of SCZ have similar etiologies. Factors such as gender, ethnicity, geography and season also have an influence on the occurrence of MS and SCZ. This paper aims to examine the differences and similarities between SCZ and MS. For this purpose, scientific papers examining various factors associated with these disorders were reviewed, and similarities and differences in genetic, immunological, seasonal, geographical, and gender-related risk factors and limited similarities in ethnic factors between the two diseases were identified. The findings suggest that subgroups of these two diseases may belong to the same class of disorders.